Opposition dynamism under authoritarianism: the case of Yemen, 1994–2011. Issue 4 (19th May 2018) - Heibach, Jens; Transfeld, Mareike
ABSTRACT: In contrast to the empirical conditions in large parts of the authoritarian world, the systematic literature on political opposition under authoritarianism either treats the opposition as a static entity or fails to comprehensively address its dynamic character. On the basis of a critical literature review and an ensuing analysis of the Joint Meeting Parties, a cross-ideological opposition alliance that gradually evolved to become the main competitor of the Salih regime in Yemen, we suggest that political opposition in electoral authoritarian regimes is an intrinsically dynamic institution in terms of its organizational shape, its goals and its modes of contestation. We also show that, while authoritarian structures do set the basic conditions defining opposition action, much of what motivates this action and contributes to opposition dynamism emerges from within the opposition. In addition, our findings on the Yemeni case suggest that opposition dynamism peaks when the strength of the opposition is nearly on par with that of the regime.